Frames selection based on modified entropy and object motion in video steganography - Muhammad, Fuad; Ernawan, Ferda (IJSTR, 2019)
Steganography schemes have been widely implemented in multimedia communication. Multimedia data, such as videos are often compressed to reduce the storage in the limited bandwidth. However, most video steganography schemes are not resistant to compression. The video provides additional hidden space in the image frame sequences. This research proposes a frame selection technique based on object motion and modified entropy in video steganography. The object motions in the video frame are determined by horizontal and vertical of motion vectors. The video frames that have object motion are computed by using modified entropy. The lowest modified entropy frames are selected for concealing a secret message. The proposed frame selections able to produce minimum distortion of stego-video compare to non-frame selection. The experimental results show that our scheme achieves good robustness of message recovery in terms of Bit Error Rate (BER) and Normalized Cross-Correlation (NC). The recovered messages of the proposed steganography scheme can survive under video compression. Â© 2019, International Journal of Scientific and Technology Research. All rights reserved.